Identifying pathogenic genetic background of simplex or multiplex retinitis pigmentosa patients: a large scale mutation screening study. Issue 7 (29th February 2008) - Jin, Z-B; Mandai, M; Yokota, T; Higuchi, K; Ohmori, K; Ohtsuki, F; Takakura, S; Itabashi, T; Wada, Y; Akimoto, M; Ooto, S; Suzuki, T; et al.
Abstract : Background and purpose: More than half of the retinitis pigmentosa (RP) cases are genetically simplex or multiplex. To date, 37 causative genes of RP have been identified; however, the elucidation of gene defects in simplex or multiplex RP patients/families remains problematic. The aim of our study was to identify the genetic causes of RP in patients with unknown or non-Mendelian inheritance. Methods and results: Since 2003, 52 simplex RP patients, 151 patients from 141 multiplex RP families, and six sporadic patients with retinal degeneration were studied. A total of 108 exons of 30 RP-causing genes that harboured the reported mutations were screened by an efficient denaturing high performance liquid chromatography (dHPLC) based assay. Aberrant fragments were subsequently analysed by automatic sequencing. Twenty-six mutations, including two frameshift mutations, one single amino acid deletion, and 23 missense mutations, were identified in 28 probands (14.07%). Eighteen mutations have not been reported to date. Three pairs of combined mutations in different genes were identified in two sporadic cases and one multiplex family, indicating the possibility of novel digenic patterns. Of the 23 missense mutations, 21 were predicted as deleterious mutations by computational methods using PolyPhen, SIFT, PANTHER, and PMut programs. Conclusion: We elucidated the mutation spectrum in Japanese RP patients and demonstrated the validity of the mutation detection system using dHPLC sequencing for genetic diagnosis in RP patients independent of familial incidence, which may provide a model strategy for identifying genetic causes in other diseases linked to a wide range of genes.